GAMBARAN KEPERCAYAAN DIRI PADA SISWA SMK ALOER WARGAKUSUMAH - Mutaharoh, Silmi; Hendriana, Heris; Supriatna, Ecep (IKIP Siliwangi, 2024)
Self Confidence is something that is needed by individual. The purpose of this study is to describe the self confidence profil of the Aloer Wargakusumah Vocational High School students. In this study using descriptive quantitative methods,the sample in this study amounted to 102 students of class XI SMK Aloer Wargakusumah. The results showed that the level of self confidence was high at 15%, low at 71% and moderate at 13%, which had aspects of self confidace that were 80% confident in their abilities 83%, optimisic 86%, responsible, 76%, rasional and realistic 72%. Meanwhile, based on gender the confidence the girl hae higher grades compared to boys, in the female gendeer self confidence dominates with a value of 55% an menas much as 45%. Thus SMK Aloer wargaksumah student generally have moderate.